Decoding Source Credibility: How it Influences Trust in Informative Brand-Related Content and Customer Purchase Intentions - Bogoevska-gavrilova, Irena; Ciunova-shuleska, Anita (My University, 2024)
Purpose As influencers build their follower base by sharing content in a particular niche (Lou and Yuan, 2019; Saima and Khan, 2020), influencer credibility greatly affects followers' perceived trust in brand-related content they share on social media (Lou and Yuan, 2019). Brand content can be categorized in various ways (Coelho et al., 2016; Luarn et al., 2015; Tafesse and Wien, 2017). Different categorizations proposed by multiple authors (Coelho et al., 2016; Luarn et al., 2015; Tafesse and Wien, 2017) identify one common type of brand-related content: informative content. Hovland and Weiss (1951) highlight the significance of the message source's credibility in enhancing the persuasiveness of the message. Influencers, seen as credible sources of information, effectively inspire shopping aspirations (Ohanian, 1990; Van der Waldt et al., 2009). Influencers’ posts serve as marketing signals to their followers i.e. potential customers given that a marketing signal is a piece of information that a customer can request and process with minimal effort (Nafees et al., 2020; Bloom and Reve, 1990). According to market signaling theory, the one who presents or represents the product to others also represents a type of marketing signal (Nafees et al., 2020; Bloom and Reve, 1990). Thus, influencers, or influential individuals (Batra et al., 1996), by demonstrating the use of a product (Spry et al., 2011) become marketing signals themselves. The effectiveness of these marketing signals is heavily reliant on the credibility of the signal sender (Herbig and Milewicz, 1996). Furthermore, source credibility is comprised of several dimensions, including expertise, trustworthiness (Hovland et al., 1953), and attractiveness (McGuire, 1985). Ohanian (1990) defines credibility as a combination of trustworthiness, expertise, and attractiveness. Lou and Yuan (2019) add an additional dimension i.e. similarity. Also, Xiao et al. (2018) emphasize a four-dimensional structure focusing on expertise, trustworthiness, likability, and similarity. By incorporating a five-dimensional credibility construct this research represents a unique approach to determining the influence of source credibility on customer’s trust in informative brand-related content and the influence of trust in brand-related content on customer’s purchase intentions. The paper is the first to use the following source credibility dimensions: trustworthiness, attractiveness, expertise, likability, and similarity. Therefore, the main motivation of this paper is to address the research gap on how influencers' credibility affects followers' trust in informative brand-related content and their subsequent purchase intentions, particularly by examining the comprehensive five-dimensional construct of source credibility, which has not yet been thoroughly explored in previous studies. The focus is on trust in informative brand-related content since social media users primarily use social networks to receive information (Edwards et al., 2002; Muntinga et al., 2011) and brand-related content shared by influencers on social networks includes information about the product (Lou and Yuan, 2019). Having in mind previously elaborated, the purpose of this study is to investigate the effect of each source credibility dimension on customers’ trust in informative brand-related content and their purchase intentions. We propose the following research hypotheses: H1: Influencers’ attractiveness positively affects trust in informative brand-related content. H2: Influencers’ trustworthiness positively affects trust in informative brand-related content. H3: Influencers’ expertise positively affects trust in informative brand-related content. H4: Influencers’ likability positively affects trust in informative brand-related content. H5: Influencers’ similarity positively affects trust in informative brand-related content. H6: Trust in informative brand-related content positively affects purchase intentions. Design/methodology/approach An online questionnaire was distributed to a purposive sample of social media users in North Macedonia. From the 380 initial responses, the final sample was refined to 307 respondents who follow influencers on social media. To test the hypotheses, we conducted a quantitative analysis of the collected data using structural equation modeling (SEM) in two phases: confirmatory factor analysis (CFA) for the measurement model and structural model testing using AMOS version 20.0. Structural equation modeling (SEM) evaluates structural relationships among various concepts or constructs, represented by multiple variables within a single integrated model (Malhotra et al., 2017). This methodology is especially prevalent in marketing research, as it enables the testing of market behaviour models (MacLean and Gray, 1998). To minimize the risk of common method bias (CMB) in the results, Harman's single-factor test was conducted, as suggested by Podsakoff et al. (2003) and Fuller et al. (2016). This test analyses the unrotated factor solution for the variables. The results indicate no dominant factor, as the single-factor solution accounts for less than 50% of the shared variance. The internal consistency of the measured variables was confirmed by calculating the Cronbach's α – coefficient for each variable (values above 0.7 as recommended by Hair et al., 2010). When conducting confirmatory factor analysis the focus is on squared multiple correlations, standardized covariance residuals, and standardized regression coefficients (Hair et al., 2006). All coefficients from the confirmatory factor analysis verified that the model aligns with the collected data. Table 1 presents the standardized regression coefficients and estimates for the hypothesized relationships. Findings According to the values in Table 1, four out of six hypotheses are confirmed. Hypotheses H1 and H3 are rejected, indicating that attractiveness and expertise do not impact customers' trust in informative brand-related content. Statistically significant relationships are found for H2, H4, H5, and H6. Likability has the strongest positive relationship with trust, followed by trustworthiness. Similarity, while the weakest of the three, still significantly influences trust. Finally, trust in informative brand-related content positively affects customers' purchase intentions. The findings partially align with the findings of Lou and Yuan (2019) that an influencer’s trustworthiness and similarity to their followers positively impact followers' trust in the influencer's branded posts, which in turn enhances purchase intentions. However, while Lou and Yuan (2019) have demonstrated the effect of attractiveness on trust, our research does not support this hypothesis. This could be because, in informative brand-related content, the emphasis is on the information itself, making physical appearance have little to no impact on the perceived value of the information. Moreover, key findings of the research of Xiao et al. (2018) include that trustworthiness is the most significant factor in determining perceived information credibility, and the similarity between the influencer and the audience, particularly in attitudes, enhances the audience's perception of the influencer's credibility. This aligns with Hovland et al. (1953), who identified similarity as a key component of source credibility, significantly influencing the persuasiveness of the message. Xiao et al. (2018) also suggest that while likability may not be the most significant factor, it enhances the overall appeal and trustworthiness of the influencer, thereby affecting trust in the brand content. Cheung et al. (2009), observed that trustworthiness in electronic word-of-mouth communications positively correlates with perceived credibility, ultimately influencing consumer attitudes and behaviours. On the other hand, several papers confirm that the relevance of attractiveness and expertise is minimal, with expertise showing virtually no impact on trust (Wiedmann and Von Mettenheim, 2020; Wang and Scheinbaum, 2018) as suggested by our research. Finally, when it comes to purchase intentions studies have shown that trust in brand-related content significantly boosts purchase intentions. Lou and Yuan (2019) found that credible influencer messages enhance consumer trust, subsequently influencing purchase intentions. These findings highlight the essential role of trust in driving customer purchases (Lou and Yuan, 2019; Liu et al., 2019) as our findings confirm. Originality/value Although social media influencers have become a communication tool for brands, there is still a lack of research on how these influencers impact their followers' perceptions of the promoted brands (Castillo and Fernández, 2019). Having in mind the brief literature review presented in this paper, no other studies previously focused on the five-dimensional construct of source credibility. Previous studies (Hovland et al., 1953; McGuire, 1985; Ohanian, 1990; Xiao et al., 2018; Lou and Yuan, 2019; Bogoevska-Gavrilova and Ciunova-Shuleska, 2022) have used the two, three, or four-dimensional source credibility construct. Furthermore, this is the first study, as known by the authors, to focus only on informative content. Previous research studies (Ducoffe, 1995; Lin and Hung, 2009; Lou and Yuan, 2019; Pollay and Mittal 1993; Petrovici and Paliwoda, 2007; Van-Tien Dao et al., 2014; Wolin et al. 2002; Bogoevska-Gavrilova, 2021) investigated predominantly informative and entertainment content value. The findings from this paper offer valuable insights for marketing managers working with influencers. Specifically, our findings indicate that if brands aim to enhance customers’ trust in product information shared on social media and subsequently boost purchase intentions, they should collaborate with influencers who are perceived as trustworthy, likable, and similar to the target audience.
Keywords: Source credibility theory; Influencer marketing; Trust in informative brand-related content; Purchase intentions